2020
DOI: 10.3390/ijms21030725
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Inflammation on Anemia in CKD Patients

Abstract: Anemia is frequently observed in the course of chronic kidney disease (CKD) and it is associated with diminishing the quality of a patient’s life. It also enhances morbidity and mortality and hastens the CKD progression rate. Patients with CKD frequently suffer from a chronic inflammatory state which is related to a vast range of underlying factors. The results of studies have demonstrated that persistent inflammation may contribute to the variability in Hb levels and hyporesponsiveness to erythropoietin stimu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
67
0
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(78 citation statements)
references
References 169 publications
(234 reference statements)
3
67
0
4
Order By: Relevance
“…6,34,64 This is of particular interest because EPO production is also impaired in human fibrotic kidneys. 7,8,40 EPO production declines in damaged kidneys despite prevalent tissue hypoxia, which should normally induce EPO expression through HIF activation. 34,[64][65][66] The reasons for insufficient EPO production in fibrotic kidneys are not completely clear, but are thought to be connected to the metaplastic transformation of interstitial EPOproducing PDGFR-β + cells into myofibroblasts.…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 99%
See 1 more Smart Citation
“…6,34,64 This is of particular interest because EPO production is also impaired in human fibrotic kidneys. 7,8,40 EPO production declines in damaged kidneys despite prevalent tissue hypoxia, which should normally induce EPO expression through HIF activation. 34,[64][65][66] The reasons for insufficient EPO production in fibrotic kidneys are not completely clear, but are thought to be connected to the metaplastic transformation of interstitial EPOproducing PDGFR-β + cells into myofibroblasts.…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 99%
“…6,[36][37][38][39] Renal fibrosis is associated with a reduced capability of the kidneys to produce erythropoietin. [5][6][7][8][9]34,40 Although the reasons for this have not yet been clearly resolved, it is thought that transformation of interstitial PDGFR-β + cells into myofibroblasts goes hand in hand with the loss of their capability to produce EPO. 5,6,34,41 In view of the major role of interstitial PDGFR-β + cells as native EPO producers and as precursors of myofibroblasts, we were interested to define the role of TGFβ1 signaling in this cell population.…”
Section: Introductionmentioning
confidence: 99%
“…HD is associated with a low-grade chronic inflammation and oxidative stress which is due to loss of antioxidants and stimulation of leukocytes during dialysis which triggers production of reactive oxygen species (ROS) [ 42 , 43 , 44 ]. Several recent studies suggested that that protective role of CST is mediated by preventing DNA damage caused by ROS, reducing endoplasmic reticulum stress-induced apoptosis and scavenging free radicals [ 45 , 46 , 47 , 48 ], while the study conducted by Aung et al implied that CST also has an immunomodulatory function, as they determined that CST has a role in inflammation by causing mast cells to release leukotrienes, prostaglandins, cytokines and chemokines [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our nding that TSAT was the independent predictor for ERI is in line with the widely accepted recognition that iron de ciency causes ESA hyporesponsiveness. In ammation can lead to ESA hyporesponsiveness [24]. Pro-in ammatory cytokines such as interleukin-6 increases the expression of hepcidin, which is the regulator of iron homeostasis [25][26].…”
Section: Discussionmentioning
confidence: 99%